Long-Term Outcomes for Arthroscopic Thermal Treatment for Scapholunate Ligament Injuries - Burn, Matthew B.; Sarkissian, Eric J.; Yao, Jeffrey (Journal of Wrist Surgery, 2020)
Background Arthroscopic electrothermal treatment of low-grade Geissler's scapholunate interosseous ligament (SLIL) tears has shown clinical benefit at short-term follow-up.Questions/Purpose This study aims to evaluate the long-term functional outcomes in patients undergoing this treatment.Patients and Methods A retrospective review of all patients treated between 2005 and 2013 was performed. Patients were excluded with less than 5 years of follow-up, the presence of static SLIL injuries, prior wrist surgery, and concomitant denervation. Symptom resolution, return to activity, postoperative complications, range of motion, grip strength, and subsequent treatment were recorded. Each patient completed Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH), Modified Mayo Wrist (MMW), and Patient-Rated Wrist Evaluation (PRWE) questionnaires.Results Nine patients underwent treatment for Geissler's grade I, II, and III SLIL injuries with a mean 7 years (range: 5–11 years) of follow-up. Mean grip strength was 99% of the nonsurgical extremity. Wrist motion was near symmetric with a mean of 76 (±14), 74 (±8), 21 (±13), and 40 degrees (±13) for wrist flexion, extension, radial deviation, and ulnar deviation. QuickDASH improved significantly by a mean 39 points (50 (preoperative)–11 [postoperative], p = 0.009). Postoperative MMW and PRWE scores were 83 and 14, respectively. Visual analog scale (VAS) score was 1.4. A total of 90% was returned to their preinjury level of function or higher.Conclusions Arthroscopic electrothermal treatment of low-grade Geissler's SLIL tears demonstrates excellent objective and subjective outcomes at a minimum 5-year follow-up, providing evidence that this is an effective, safe, and, most importantly, durable-therapeutic modality. Level of Evidence This is a Level IV, case series study.
Keywords: capsulorrhaphy; electrothermal; shrinkage; scapholunate; wrist